Pengaruh Tele-Edukasi Masa Nifas Berbasis WhatsApp terhadap Peningkatan Pengetahuan dan Sikap Perawatan Diri Ibu dalam Perspektif Kesehatan Reproduksi: Kesehatan Reproduksi Pada Masa Nifas - Junawalia Mayang Sari; Umi Solekah; Mariyam; M Iman Tarmizi Thaher (Jurnal Kesehatan dan Pembangunan, 2026)
The postpartum period is an integral part of the female reproductive health cycle, characterized by the recovery of reproductive organs and physical, psychological, and social adaptation following childbirth. Failure to recognize postpartum danger signs and to practice appropriate self-care contributes to an increased risk of maternal morbidity and mortality. Limited access to postnatal health services necessitates sustainable and easily accessible alternative educational approaches. The utilization of communication technology through the WhatsApp application offers a strategic opportunity to deliver individualized and continuous reproductive health education. This study aimed to analyze the effect of WhatsApp-based postpartum tele-education on improving mothers’ knowledge and attitudes toward self-care from a reproductive health perspective. This study employed a pre-experimental one-group pretest–posttest design involving 30 postpartum mothers who met the inclusion criteria. The intervention was delivered over seven consecutive days using structured educational materials covering postpartum self-care, reproductive danger signs, nutrition, postpartum mental health, and prevention of postpartum complications. Data analysis was conducted using the Shapiro–Wilk test and paired t-test. The results showed a significant increase in postpartum mothers’ knowledge (p < 0.001) and attitudes (p < 0.001) after the intervention. The proportion of mothers with good knowledge increased from 0% to 83.3%, while positive attitudes toward self-care increased from 0% to 96.7%. These findings indicate that WhatsApp-based tele-education is effective in promoting reproductive health. WhatsApp-based postpartum tele-education effectively improves mothers’ knowledge and attitudes toward self-care and serves as a reproductive health promotion strategy to support safe and sustainable postpartum recovery.